Bioinformatics Analysis and Identification of Phytoene Synthase Gene in Microalgae - Shaker, Saeedeh; Morowvat, Mohammad H.; Ghasemi, Younes (Recent Patents on Biotechnology, 2021)
Background: Carotenoids are known as lipophilic secondary metabolites with important biological activities, which are mostly used in the food and pharmaceutical industry. They contribute to the colours of many fruits and flowers. Studies on the biosynthetic pathways of isoprenoids and carotenoids are still scarce, especially in microalgae and are limited to specic groups. Dunaliella spp. in Chlorophyta taxon of algae, the 2-C-methyl-D-erythritol 4-phosphate/ 1-deoxy-D-xylulose 5-phosphate (DOXP/MEP) is the synthesis pathway of sterols and carotenoids. Objectives: In this study, we used 12 Psy gene sequences in Dunaliella sp., also Scenedesmus acutus and Diospyros kaki to investigate a genome-wide search. The results are useful for better identification of carotenoids metabolisms, and increasing the production rate of beta-carotene in pharmaceutical, food and industrial processes. Methods: Phytoene synthase (Psy) from Dunaliella spp. was selected as the rst regulatory point in the carotenoids pathway that catalysis the formation of geranylgeranyl pyrophosphate in isoprenoid biosynthesis. Structural, evolutionary and physics-chemical characteristics were investigated, using various bioinformatics tools and computer techniques. Moreover, some recently published patents were also regarded. Results: The maximum length of the conserved motif was 5167 bp for Dunaliella. sp. (DQ463306.1) and the smallest length of the conserved motif was 416 bp belonging to D. salina (JQ762451.1). The average molecular weight of species was 41820.53 Da. The theoretical pI of species varied from 4.87 to 9.65, indicating vernation in the acidic nature. Two strains of D. bardawil (U91900.1 and EU328287.1) showed just a long-distance relationship with all other Dunaliella strains. Whilst, D. parva displayed the furthest vicinity with all the studied strains. Conclusion: Our study highlighted the Psy regulatory mechanism, as a key factor in the carotenoids pathway, to facilitate genetic and metabolic engineering studies. The obtained tree-dimensional arrangement of the amino acids revealed the regional structures and folding of the diverse segments of helices, sheets and turns. This information is a key point to unveil the protein's operation mechanism. Besides, we confirmed the suitability of bioinformatic approaches for analysing the gene structures and identifying the new Psy genes in unstudied microalgal strains.
Keywords: synthetic biology